ANALYSIS OF THE ROLE OF THE DIRECTORATE GENERAL OF CUSTOMS AND EXCISE IN SUBCONTRACT APPROVAL SERVICES IN BONDED AREAS DURING THE PANDEMIC IN ORDER TO IMPLEMENT THE PROGRAM NATIONAL ECONOMIC RECOVERY - Retto Djong, Alexander Mario (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
The author conducts an analysis of the role of the Yogyakarta Customs and Excise Supervision and Services Office of Type B, Yogyakarta in subcontract approval services in Bonded Zones during the pandemic to implement the National Economic Recovery program. The method used by the author is a descriptive qualitative approach using literature and field observation methods. From the research results, it was concluded that KPPBC TMP B Yogyakarta has had innovations in providing subcontract approval services during this pandemic. However, it is hoped that the application that has been used will not burden business actors too much. So that in the future improvements must continue to be made by KPPBC TMP B Yogyakarta so that business actors will be more motivated in running their businesses and increase the value of exports which will be directly proportional to National Economic Recovery